Progresses and challenges in sulfur autotrophic denitrification-enhanced Anammox for low carbon and efficient nitrogen removal. Issue 24 (28th September 2022) - Li, Xiang; Shi, Miao; Zhang, Mao; Li, Wei; Xu, Pei-lin; Wang, Yayi; Yuan, Yan; Huang, Yong
Abstract: Autotrophic nitrogen removal couple process based on anaerobic ammonium oxidation (Anammox) has been applied to treat various high-ammonia and low-carbon wastewater for its advantageous ability to remove nitrogen. However, high concentrations of NO 3 − -N in the effluent is a drawback that prevents the total nitrogen from meeting the discharge standard. For this reason, coupling sulfur autotrophic denitrification (SADN) with Anammox for the advanced treatment of NO 3 − -N to achieve a completely autotrophic biological nitrogen removal process that is independent of organic matter has become a major focus of research in recent years. To reduce SO 4 2− -S in the SADN process, the short-cut SADN (SSADN) process was pioneered for controlling NO 3 − -N reduction in the NO 2 − -N phase. This method also serves as an efficient anaerobic autotrophic process that simultaneously removes biological nitrogen from wastewater containing NH 4 + -N and NO 3 − -N. This article reviews the control parameters of SSADN and the forms of coupling with Anammox, analyze the directional transformation of nitrogen and sulfur in the coupling process and the complex competition of substrates, and finally evaluate application bottlenecks that limit its industrialization, which are necessary to address for furthering the development of this process. Graphical abstract: UF0001